Cetuximab-modified silica nanoparticle loaded with ICG for tumor-targeted combinational therapy of breast cancer. (1st January 2019) - Zhang, Xiaoxue; Li, Yinyan; Wei, Minjie; Liu, Chang; Yang, Jun
Abstract: Combinational therapy is usually considered as a preferable approach for effective cancer therapy. Especially, combinational chemo and photothermal therapy is of particular interest due to its high flexibility as well as efficiency. In this article, we the silica nanoparticles (SLN) were surface conjugated with Cetuximab (Cet-SLN) to target epidermal growth factor receptor (EGFR), a common receptor that usually observed to overexpress in multiple breast cancers. Moreover, the high drug loading capacity of Cet-SLN was employed to encapsulate photothermal agent indocyanine green (ICG) to finally fabricate a versatile drug delivery system (DDS) able to co-deliver Cet and ICG (Cet-SLN/ICG) for combinational chemo-photothermal therapy of breast cancer. The obtained results clearly demonstrated that Cet-SLN/ICG was well-dispersed nanoparticles with preferable stability under physiological condition. Furthermore, due to the conjugation of Cet, Cet-SLN/ICG could target EGFR which overexpress in MCF-7 cells. Most importantly, both in vitro and in vivo results suggested that compared with Cet or ICG alone, the Cet-SLN/ICG showed superior anticancer efficacy. In conclusion, Cet-SLN/ICG could be a potential platform for effective combinational chemo-photothermal therapy for breast cancer.